Expression of Mycobacterium tuberculosis Protein Tyrosine Phosphatase B in Escherichia coli and Its Recovery from Inclusion Body - Lalu Rudyat Telly Savalas; Prapti Sedijani; Saprizal Hadisaputra; Jannatin Ardhuha; Chomsa Asih Lestari; Etty Nurul Wahidah (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2017)
The present study aims at expressing and partially purifying PtpB in active form. To achieve this, Mtb PtpB gene has been cloned into pET30a vector and overexpressed in Escherichia coli BL 21(DE3) under IPTG induction in the form of an inclusion body. Following resolubilization by urea and dialysis, the resulted PtpB has been shown to be active against para-Nitrophenyl phosphate. It is concluded that the resulted PtpB has had been recovered from inclusion body to give the active form of the enzyme, and thus the success in overexpressing PtpB provides the required material to investigate the biochemical properties of the pathogen virulence factor further.